Guide to the census - Bass, Frank (Wiley, 2013)
Written by a veteran journalist and Bloomberg data editor ("an information behemoth—a news aggregator, government contract database, Congressional staff directory, and source for policy research and analysis all in one website." —New York Times), Guide to the Census gives you the knowledge and tools you need to access and successfully navigate Census data and explores the nearly limitless ways in which that data can be leveraged to market your products or services, grow your company, and promote every aspect of your company's success.